METTL3-mediated SNHG1 m6A modification promotes proliferation and migration through transcriptional regulation of WDR74 in osteosarcoma - Qiu, Guanzhen; Bao, Yuxin; Zhang, Yuanzhuang; Xu, Yeqiu; Qiao, Tianhua; Li, Chenghao; Zhai, Hanjie; Chen, Zhenjun; Ren, Fu; Wang, Yong (Frontiers in Oncology, 2025)
IntroductionAs the most prevalent internal RNA modification in eukaryotic transcripts, N6-methyladenosine (m6A) which is catalyzed by methyltransferase-like 3 (METTL3), is widely involved in cancerous diseases. However, the role of METTL3 and small nucleolar RNA host gene 1 (SNHG1) playing in osteosarcoma (OS) remains largely unknown.MethodsBioinformatics analysis, RT-qPCR, western blotting assays were used to detect the expression of METTL3, SNHG1, RNA binding motif protein 15 (RBM15), WD repeat domain 74 (WDR74) and EWS RNA binding protein 1 (EWSR1) accordingly. Cell proliferation and motility ability changes were assessed by colony formation and transwell migration assays. RNA stability changes were evaluated by an actinomycin D assay. The level of SNHG1 m6A modification changes were addressed by an RNA immunoprecipitation (MeRIP)-qPCR assay. RNA pulldown assays and RNA immunoprecipitation assays were applied to detect the interactions between SNHG1 and proteins. A chromatin immunoprecipitation (ChIP)-qPCR assay was performed to verify the binding effect between WDR74 promoter region and EWSR1. Orthotopic xenograft mouse models were constructed to evaluate the role of METTL3 playing in OS tumorigenesis and lung metastasis in vivo.ResultsIt was uncovered that METTL3 was significantly upregulated in OS tissues and cell lines. As an oncogenic regulator, METTL3 promoted proliferation and migration in OS cells by enhancing the stability of SNHG1. Mechanically, it was displayed that METTL3 catalyzed SNHG1 m6A modification with the assistance of RBM15. More deeply, it was found that SNHG1 promoted OS cells proliferation and migration via regulation of its neighboring gene WDR74. Meanwhile, it was discovered that SNHG1 affected WDR74 transcription by EWSR1 recruitment. Finally, it was displayed that overexpression of METTL3 promoted SNHG1 and WDR74 expression, and upregulation of METTL3 facilitated OS tumorigenesis and lung metastasis in vivo.ConclusionThe present research illustrated that METTL3 enhanced the stability of SNHG1 with the assistance of RBM15 in an m6A dependent manner in OS cells. And SNHG1, promoted the transcription of WDR74 in cis, via recruitment of EWSR1, thereby facilitated WDR74-mediated proliferation and migration in OS cells. These findings provide new insights into the epigenetic regulation of OS and highlight potential therapeutic targets.